Biochemistry - Campbell, Mary K. (Boston, MA. : Cengage Learning, 2018)
Provides a comprehensive introduction to biochemistry, covering structure and function of biomolecules, metabolism, and molecular biology principles.
Includes bibliographical references and index
Keywords: Biochemistry; Molecular biology; Metabolism